Development of an e-Module Based on a Discovery Learning Model on Form and Function of Body Parts in Plants at Grade IV Elementary School Level - Fitri Khoiroh Sayidah Harahap; Humairoh Sakinah Zainuri; Novia Rahmadani; Siti Fadilla; Windi Melisa; Riska Fadhilah Hutasuhut (Yayasan Zia Salsabila, 2023)
This research aims to determine the effectiveness of e-module development in the science learning process at the fourth grade elementary school level, especially in the material